Development of Partial Discharge Detection Device for PD Detection on Medium Voltage XLPE Cable - Mohamad Radzi M.I.F.M.; Ahmad M.R.; Nik Ali N.H.N.; Ariffin A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Acoustic emission testing; Cables; Costs; Flexible electronics; Printed circuit boards; Ultrasonic applications; Degradation of insulations; Detection device; High frequency signals; High-voltage equipments; Higher-frequency signals; Insulation materials; Medium voltage; Natural phenomenon; Partial discharge detection; XLPE cables; Partial discharges